Eco-Friendly Product Purchasing Behavior Based on the Theory of Consumption Value - Bernadetta Diansepti Maharani; Lusia Tria Hatmanti Hutami; Dika Prawita; Budi Setiawan; Friska Putri Wati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates eco-friendly product purchasing behavior among millennial consumers based on the Theory of Consumption Value. Using a quantitative approach and multiple regression analysis, the research examines the effects of functional, conditional, social, epistemic, and emotional values on green purchase intention, as well as the effect of green purchase intention on green purchase behavior. The findings show that social value and emotional value significantly influence green purchase intention, while functional, conditional, and epistemic values have no significant effect. Moreover, green purchase intention positively affects green purchase behavior. These results highlight that millennials’ eco-friendly purchasing decisions are primarily driven by emotional concern and social influence rather than by product functionality or situational factors.